The transition to digital television in Greece: Now what?. (1st March 2014) - Papathanassopoulos, Stylianos
This article aims to provide an overview of the current state of digital television in Greece. By examining the latest digital developments in the middle of financial crisis, it suggests that the Greek government adopted a purely market-driven approach leaving the private forces to take up digital terrestrial television. The closure of the public broadcaster, ERT, has accelerated the neo-liberal market-driven policy and Greece has ended up as one of the countries that have left the development of digital terrestrial television entirely to the private sector.